Characteristics of Familial Melanoma in Valencia, Spain, Based on the Presence of CDKN2A Mutations and MC1R Variants - Claudia Huerta; Zaida Garcia-Casado; José Bañuls; Manuel Moragon; Vicente Oliver; Blanca Unamuno; Celia Requena; Rajiv Kumar; Eduardo Nagore (Medical Journals Sweden, 2018)
Melanoma results from a complex interplay between environmental factors and individual genetic susceptibility. Familial melanoma is attributable to predisposition genes with variable penetrance. The aim of this study was to identify differences between familial melanoma and sporadic cases in our population, based on the presence of CDKN2A mutations and MC1R variants. Comparing 107 patients with familial melanoma from 87 families (17% CDKN2A mutated) with 1,390 cases of sporadic melanomas, the former were younger and exhibited an increased prevalence of atypical naevi and squamous cell carcinoma (SCC). CDKN2A mutation carriers presented more atypical naevi, multiple melanomas, and basal cell carcinoma, while non-carriers were more likely to have light-coloured hair, atypical naevi, and SCC. MC1R variants decreased the age at diagnosis in all groups and were associated with an increased prevalence of SCC, especially in patients with familial melanoma without CDKN2A mutations. These characteristics may help to establish prevention measures targeting patients with familial melanoma in the Mediterranean area.